International Perspectives in Undergraduate Education - Stiglitz, Joseph E. (American Economic Review, 1993)
There is an old joke about economics which says that the questions stay the same, only the answers change. Though there is some truth in that idea, I would argue that over the past 50 years, there have been marked changes both in the questions and in the answers, but that many of these changes are still only imperfectly reflected in undergraduate textbooks.